OP0063 From Childhood to Adulthood: Longitudinal Trajectory of Damage in Patients with Childhood-Onset Systemic Lupus Erythematosus (CSLE). (9th June 2015) - Lim, L.S.H.; Pullenayegum, E.; Lim, L.; Gladman, D.D.; Feldman, B.M.; Silverman, E.D.
Abstract : Background: Outcomes of patients with cSLE over time and into adulthood are poorly understood. There has been no information about the longitudinal trajectory of organ damage in cSLE patients. Objectives: 1) To determine the longitudinal damage trajectory– as measured by the SLE damage index (SDI)– in patients with cSLE. 2) To identify both baseline and disease course (time-varying) predictors of damage trajectory. Methods: Single centre, retrospective, inception cohort. We included 473 patients who were diagnosed and followed, from 1st January 1985 to 30th September 2011. To be included, patients had to be <18 years at diagnosis, have satisfied the ACR classification criteria for SLE, were treated for ≤3 months with steroids or an immunosuppressant for any other disease, and have had at least 3 visits. Longitudinal pediatric-age data was obtained from our research database while adult-age data was obtained from either a research database or patients' charts. Clinical information at every visit was collected: for SLE disease activity index 2000 (SLEDAI2K), the SDI, laboratory results, and medications. Longitudinal trajectory of damage fit best with a 2nd order fractional polynomial (0.5, 1). Predictors were identified using a weighted generalized estimating equation (WGEE). Time-varying predictors: disease activity, individual items of SLEDAI2K, corticosteroid, immunosuppressant and antimalarial exposures, were lagged by 6, 12, 18 and 24 months in different models. Results: 67/473 (14%) patients were lost to follow-up. There were 14097 visits, totaling 3290 patient-years. The median follow-up duration was 5.5 years. The median age at diagnosis was 14.1 years and median age at last visit was19.5 years (range 6.0–41.9 years). 65% of patients were >18 years old at last follow-up. The predicted average population damage was 0.7 at 5 years, 1.3 at 10 years, 1.9 at 15 years, 2.3 at 20 years and 2.7 at 25 years. Cataract (14%) was the most common item of damage, followed by avascular necrosis (10%) and osteoporosis (5%). Only 2 patients had a myocardial infarction. Older age at diagnosis and earlier time-periods of diagnosis predicted higher initial damage but did not significantly affect the trajectory of damage over time. Life-threatening major organ manifestations predicted higher initial damage but the accrual of damage slowed down over time. By contrast, patients without major organ involvement steadily gained damage over time. Clinical features that predicted a subsequent increase in the damage trajectory were: acute confusion state (24 mos before), lupus headaches (6, 12 mos before) and fever (18 mos before). The higher the prednisone dose (12, 24 mos before) and the use of cyclophosphamide (6, 18, 24 mos before) were also associated with an increased damage trajectory. Antimalarial exposure (6 mos before) was protective against an increase in damage trajectory. Conclusions: Patients with cSLE accrue damage steadily throughout their disease course into adulthood. We identified the baseline factors that predicted higher initial damage and influence damage trajectory. Over time, SLE clinical features and therapeutic exposures during the course of disease, predicted a change in damage trajectory. Disclosure of Interest: None declared